Anisotropic deformation of 4H-SiC wafers: insights from nanoindentation tests. (8th December 2022) - Liu, Xiaoshuang; Wang, Rong; Zhang, Junran; Lu, Yunhao; Zhang, Yiqiang; Yang, Deren; Pi, Xiaodong
Abstract: In this work, the anisotropic deformation and anisotropic mechanical properties of 4H silicon carbide (4H-SiC) single crystal wafers are proposed by using nanoindentation. The C face of a 4H-SiC wafer has higher hardness and lower fracture toughness than those of the Si face. Because the deformation of 4H-SiC is assisted by the nucleation and slip of basal plane dislocations (BPDs), especially the slip of Si-core partial dislocations (PDs) of the BPDs, the nucleation and slip of the Si-core PDs in the Si face of 4H-SiC is easier than those in the C face, which releases the nanoindentation-induced stress and results in the decrease of the hardness and increase of the fracture toughness of the Si face of 4H-SiC wafers. Due to the hexagonal lattice of 4H-SiC, the hardness along < 1 1 ˉ 00 > of 4H-SiC is higher than that along < 11 2 ˉ 0 >, but the fracture toughness along the < 1 1 ˉ 00 > is lower than that along the < 11 2 ˉ 0 >, as a result of the enhanced glide of dislocations along the most closely-packed direction. The insights gained in this work are expected to shed light on the optimization of the mechanical processing of 4H-SiC wafers.